Studi Kajian: Memahami Teamwork - Alfarialda, Elda Riska; Annisa, Annisa; Ahmad, Alisha; Triyana, Tamam Devi; Wardhana, Mada Aditia (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2025)
This research analyzes scientific publication trends on teamwork (2016–2025) through a bibliometric approach. Data from 1,420 documents sourced from Scopus, Crossref, and Google Scholar are analyzed quantitatively (descriptive statistics, LDA) and qualitatively (thematic interpretation). Results indicate peak research productivity in 2018 (206 publications), followed by a significant decline until 2023, suspectedly due to the pandemic or research focus shifts. Keyword analysis identifies three dominant clusters: (1) education ("student", "educ", 15.04% occurrence of "teamwork"), (2) healthcare ("care", "patient"), and (3) organization ("leadership", "safeti"). Topic classification reveals six main themes: contextual effectiveness (25%, especially healthcare/IT), team training (18%), interprofessional collaboration (17%), methodological innovation (14%), non-technical skills (13%), and supporting technology (13%). Theoretically, the findings map literature fragmentation and a shift towards applied approaches. Practically, the research highlights the urgency for training based on psychological safety, cross-disciplinary communication, and AI integration. Limitations include Western context bias and the need to investigate causes of the post-2018 publication decline.